2022
DOI: 10.3390/toxins15010006
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Disrupting Activity of Cobra Cytotoxins Is Determined by Configuration of the N-Terminal Loop

Abstract: In aqueous solutions, cobra cytotoxins (CTX), three-finger folded proteins, exhibit conformational equilibrium between conformers with either cis or trans peptide bonds in the N-terminal loop (loop-I). The equilibrium is shifted to the cis form in toxins with a pair of adjacent Pro residues in this loop. It is known that CTX with a single Pro residue in loop-I and a cis peptide bond do not interact with lipid membranes. Thus, if a cis peptide bond is present in loop-I, as in a Pro-Pro containing CTX, this shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Liposomes were composed of phosphatidyl choline (100% PC). The method was mainly referred as references ( 70 , 71 ) with some modifications. PC (Picasso) was dissolved in a methanol/chloroform mixture at a 1:9 ratio with a final concentration of 35 mg/ml and protected from light in distillation flasks.…”
Section: Methodsmentioning
confidence: 99%
“…Liposomes were composed of phosphatidyl choline (100% PC). The method was mainly referred as references ( 70 , 71 ) with some modifications. PC (Picasso) was dissolved in a methanol/chloroform mixture at a 1:9 ratio with a final concentration of 35 mg/ml and protected from light in distillation flasks.…”
Section: Methodsmentioning
confidence: 99%
“…The first, and so far unique, among three-fingered toxins, glycosylated cytotoxin was isolated from cobra N. kaouthia venom, where the glycosylation of Asn29 in loop II resulted in a decrease in its biological activity [ 9 ]. It was found that the cytotoxicity depended on the structure of loops I and II, the toxins with two adjacent proline residues in loop I being the least active [ 78 , 79 ]. Using the confocal spectral imaging technique and fluorescently labeled cytotoxins, it was shown that cytotoxins penetrated readily into cells and accumulated markedly in the lysosomes, and this accumulation correlated well with the cytotoxic effects [ 79 ].…”
Section: Other Snake Venom Toxinsmentioning
confidence: 99%
“…Copyright© Edward S Gasanoff Cytotoxins CTI and CTII, membrane-active cationic proteins of 7 kD from the Central Asian cobra venom, have been widely used in studies to probe the structural organization of model lipid membranes [21,45,[57][58][59][60][61][62][63][64][65][66][67]. Both cytotoxins phenocopy membranotropic properties of C8 subunit of the F0 sector in bovine ATP synthase [9,61].…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…It has been shown that CTII decreases the angular anisotropy of the spin-label EPR spectral signals in lipid films enriched with acidic phospholipids, while CTI demonstrates the same ability only in lipid films enriched with CL, but not with other acidic phospholipids [59]. Both CTI and CTII trigger aggregation of liposomes and dehydration of the membrane surface [45,[57][58][59][60][61]. CTII induces intermembrane exchange of lipids and membrane fusion in membranes enriched with any kind of acidic lipids, while CTI is able to do the same only in membranes enriched with CL [45,[57][58][59][60][61][65][66][67][68].…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
See 1 more Smart Citation